2003
DOI: 10.1038/sj.bjc.6600952
|View full text |Cite
|
Sign up to set email alerts
|

The LIM-only protein, LMO4, and the LIM domain-binding protein, LDB1, expression in squamous cell carcinomas of the oral cavity

Abstract: Carcinoma cells can lose their epithelial cell characteristics and dedifferentiate into a fibroblast-like cell during progression of a neoplasm. Aberrant expression of oligomeric transcriptional complexes contributes to progression of carcinomas. Although individual transcription factors initiating progression remain unknown, LIM-only protein (LMO) and LIM-domain binding protein (LDB) negatively regulate breast carcinoma cell differentiation. In this study, we investigated the expression of LMO4 and LDB in squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 44 publications
4
46
0
Order By: Relevance
“…Consistent with a role in mammary epithelial cells, we have shown that overexpression of a dominantnegative LMO4 inhibits ductular and lobuloalveolar development in the mammary glands of transgenic mice (Wang et al, 2004), and others have demonstrated that mammary gland-specific deletion of the LMO4 gene leads to impaired lobuloalveolar development during pregnancy (Sum et al, 2005c). LMO4 has also been shown to be upregulated at the invasive fronts of oral cancers, suggesting a role in cancer cell invasion (Mizunuma et al, 2003). In the prostate, LMO4 was downregulated during tumor progression and lowered in hormone refractory tumors (Mousses et al, 2002).…”
Section: Lmo4 Modulates Tgfb Signaling Z Lu Et Almentioning
confidence: 62%
“…Consistent with a role in mammary epithelial cells, we have shown that overexpression of a dominantnegative LMO4 inhibits ductular and lobuloalveolar development in the mammary glands of transgenic mice (Wang et al, 2004), and others have demonstrated that mammary gland-specific deletion of the LMO4 gene leads to impaired lobuloalveolar development during pregnancy (Sum et al, 2005c). LMO4 has also been shown to be upregulated at the invasive fronts of oral cancers, suggesting a role in cancer cell invasion (Mizunuma et al, 2003). In the prostate, LMO4 was downregulated during tumor progression and lowered in hormone refractory tumors (Mousses et al, 2002).…”
Section: Lmo4 Modulates Tgfb Signaling Z Lu Et Almentioning
confidence: 62%
“…LMO2 regulates angiogenesis and hematopoiesis (8,9), and LMO1 and LMO3 are expressed during embryogenesis (10). LMO proteins have important roles in cell growth, apoptosis, and differentiation (11)(12)(13). A previous study showed that LMO4 is overexpressed during the differentiation of mammary epithelial cells (14), implicating it as an oncogene.…”
Section: Discussionmentioning
confidence: 99%
“…LMO4 has been implicated in the cause or progression of breast cancers (Sum et al, 2005b), squamous cell carcinomas of oral cavity (Mizunuma et al, 2003) and primary prostate cancers (Mousses et al, 2002). The LMO4 gene is most highly expressed in mammary epithelial cells during midpregnancy (Wang et al, 2004), a stage of active proliferation and invasion; interference with the protein (Wang et al, 2004) or deletion of the gene (Sum et al, 2005c) leads to impaired lobuloalveolar development of the mammary gland.…”
Section: Introductionmentioning
confidence: 99%